Arhitectura rurală din zona etnografică a Târnavelor. Studiu de caz: satul Bălcaciu/Bulkesch/Bolkács – între tradiție și modernitate - Maria LAZĂR (Eon, 2025)
This paper illustrates the architectural characteristics of the “Târnava Mică” ethnographic zone, with a focus on Bălcaciu, a village in the region. The area has a complex historical evolution that is reflected in the village’s architecture. Due to fairly recent historical events, there was a dramatic demographic shift clearly mirrored in the village’s appearance. The oldest building in the village, the Evangelical church, originally built in the XVth century, stands as a beautiful example of a medieval fortified church, such as others that can be found all over Transilvania. The current architectural landscape of this rural community is a result of its historical evolution, but also of the blending of multiple ethnic groups throughout the years: Romanians, Saxons, Hungarians and the Roma people. At the moment, houses that are newly built rarely follow traditional rules or include traditional elements. Rather, the rise of globalisation has a visible impact on current architectural trends that are borrowed from abroad and included in this small Transilvanian village.